Safe mobility : challenges, methodology and solutions - Lord, Dominique, 1969-; Washington, Simon (Transport and sustainability ;, 2018)
Safe mobility is clearly linked to transport sustainability, as fatalities and injuries resulting from people engaged with transport networks increasingly becomes a public health concern, relative to other health threats. This volume presents the current state of the knowledge across a multitude of analytical and context specific transport safety areas. It includes a comprehensive set of chapters authored by many of the world's leading experts in both behavioural and engineering aspects of safety mobility. The book increases the level of knowledge on road safety contexts, issues and challenges; shares what can currently be done to address the variety of issues; and points to what needs to be done to make further gains in road safety.